Theoretical study on the insertion reaction of CH(X2) into the oh bond in n-C4H9OH - Nguyen Trong Nghia; Nguyen, Duc-Trung; Pham Van Tien; Nguyen Thi Minh Hue (Vietnam Journal of Science and Technology, 2023)
CH radicals play an important role in the combustion of hydrocarbon. The insertion mechanism of a CH radical into the O-H bond of n-C4H9OH is investigated theoretically by a detailed potential energy surface calculation at the BHandHLYP/6-311++G(3df,2p) and CCSD(T)/6-311++G(d,p) (single-point) levels. Our results show that the CH radical attacks into the oxygen atom in n-C4H9OH to form a prereaction complex (COMP) to be followed by an insertion of the CH radical into the O-H bond of the n-C4H9OH molecule to form the low-lying intermediate IS1 (CH2OCH2CH2CH2CH3). This intermediate can isomerize to form IS2 (CH3OCH2CHCH2CH3), IS3 (CH3CH2CH2CH2CH2O), and IS4 (CH3CH2CH2CH2CHOH). These intermediates can decompose to yield 9 products (PR1-PR9) in which major ones are PR1 (CH2CH2CH2CH3 + CH2O), PR2 (CH2CHCH2CH3 + CH3O) and PR3 (CH2CHCH2OCH3 + CH3).